Neuroprotective effect of salvianolate lyophilized injection against cerebral ischemia in type 1 diabetic rats - Fujiang Wang (BMC Complementary and Alternative Medicine, 2017)
Abstract Background Salvianolate lyophilized injection (SLI) has been clinically used in China for the treatment of acutely cerebral infarction. Clinical and experimental studies have shown that Diabetes mellitus (DM) not only increases the risk of ischemic stroke recurrence but also leads to poor outcomes and increases fatality rates after stroke. Our previous study has proved that SLI can reduce the infarct volume after stroke in type 1 diabetic rats. The aim of the study is to explore the mechanism of SLI on stroke outcome in type 1 diabetic (T1DM) rats. Methods Type 1 diabetes rats model (T1DM) was induced in male Wistar rats by intraperitoneal (i.p) injection of streptozotocin (60 mg/kg) and T1DM rats were subjected to intraluminal middle cerebral artery occlusion (MCAO). The T1DM + MCAO rats were randomly divided into six groups: sham-operated, model-vehicle, positive control group (Edaravone-treating, DE 6 mg/kg) and SLI-treating group (10.5 mg/kg, 21 mg/kg and 42 mg/kg). SLI and DE were administered by tail vein injection at 3 h after MCAO, then daily for 14 days. Micro-CT scans of the brain tissue revealed vessel characteristics and distribution in the ischemia zone. Glucose uptake was analyzed by PET/CT. RAGE, MMP9 and inflammatory factors (COX-2, TNF-α and ICAM-1), HQ-1, HQO-1 and Nrf-2 expression levels in the ischemic brain tissue were analyzed by Immunofluorescence staining and Western blot at 14 days after MCAO. Results In this study, we have demonstrated that SLI treatment significantly increased the number of brain microvasculature in ipsilateral and glucose uptake in cortex, hippocampus and penumbra in the T1DM + MCAO rats. SLI also significantly decreased the expression of RAGE, MMP9 and inflammatory factors expression, and increased the expression of HQ-1, HQO-1 and Nrf-2 in T1DM + MCAO rats. Conclusion The study showed that SLI could protect against cerebral ischemia injury in T1DM + MCAO rats and the mechanism is related to decrease inflammatory factors and activate of the Nrf2/HO-1 signaling pathway.